Assessment of Ogun State Agricultural Multi-Purpose Credit Agency Loan Delivery to Crop Farmers in Ogun State, Nigeria - Agbelemoge, Adeyanju; sogaolu, Elisha Oyedele (NIU Journal of Humanities, 2020)
The study assessed the delivery of Ogun State Agricultural Multipurpose Credit/loan to crop farmers in Ogun State. A multi-stage random sampling technique was used to select one hundred and six crop farmer beneficiaries from the four zones. Interview schedule was used to collect primary data. The data were analyzed with descriptive statistics such as frequencies and percentages and inferential statistics were chi-square and regression analysis. The results revealed that respondents were mostly male of average age of 45years, married and averagely educated with 25years of farming experience and cultivated average of 5 hectares of farmland. Radio was the commonest source of information (`x =2.10) followed by friends and neighbours (`x =2.08) and Extension Agents (`x =2.05). Regression analysis revealed positive significant relationship between perception of effectiveness of OSAMCA activities and factors that motivated crop farmers` loan repayment such as linkage with Insurance company (t = 2.30); Extension Agents` advisory services (t = -2.75) and organization of seminars (t =0.41). Many problems were encountered such as delay in disbursing the loan amount (`x =2.30) and inadequacy of the amount of loan given (`x =2.28).The respondents perceived the activities of OSAMCA as positive and effective. Upwards review of loan amount was recommended. Keywords: Accessibility criteria, Assessment, Crop farmers, Ogun state, OSAMCA loan